John Cheever's relationship with the American magazine marketplace, 1930 to 1964 - Monkman, James (2015)
John Cheever published over two hundred short stories in an array of small-, mid-, and large-circulation magazines between 1930 and 1981. One hundred and twenty of these stories appeared in The New Yorker. During Cheever’s career and since his death in 1982, many critics have typically analysed his short stories in isolation from the conditions of their production, lest Cheever’s subversive modernist tendencies be confused with the conservative middlebrow ethos of The New Yorker, or the populist aspect of other large-circulation magazines. Critics, including Cheever’s daughter and his most recent biographer Blake Bailey, also claim that Cheever was a financial and, ultimately, artistic victim of the magazine marketplace. Drawing on largely unpublished editorial and administrative correspondence in the New Yorker Records and editorially annotated short story typescripts in the John Cheever Literary Manuscripts collection, and using a historicised close-reading practice, this thesis examines the influence of the magazine marketplace on the short fiction that Cheever produced between 1930 and 1964. It challenges the critical consensus by arguing that Cheever did not dissociate his authorship from commerciality at any point during his career, and consistently exploited the magazine marketplace to his financial and creative advantage, whether this meant temporarily producing stories for little magazines in the early 1930s and romance stories for mainstream titles in the 1940s, or selling his New Yorker rejections to its rivals, which he did throughout his career. Cheever also developed strong working relationships with his editors at The New Yorker during the 1940s and 1950s. This thesis re-evaluates these relationships by analysing comparatively the drafts, archival materials that have hitherto been neglected by critics, and published versions of some of Cheever’s best known New Yorker stories. In so doing, this thesis demonstrates the crucial role that editorial collaboration played in Cheever’s writing process.